Quality Oil Company. J. E. Marshall's Shell Service Station on Rural Hall Road. - Unknown (Forsyth County Public Library, 2008)
Photo was made in the 1930s. The Quality Oil Company granted permission to the Forsyth County Public Library to reproduce these images for the collection and to make them available on Digital Forsyth.
Quality Oil Company. J. E. Marshall's Shell Service Station on Rural Hall Road.
Keywords: Digital Forsyth; Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works